2010
DOI: 10.1148/radiol.10090968
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Real-time US with CT Images to Guide Sacroiliac Joint Injection in Vitro and in Vivo

Abstract: Image fusion of real-time US and previously obtained CT scans is feasible to guide needle insertion into the SI joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 27 publications
3
47
0
1
Order By: Relevance
“…Our experience confirms previous reports on the efficacy of image fusion as a guide for sacroiliac joint injections [12] and provides the first data on the feasibility of US-MR image fusion for this purpose. Aside from the advantages of three-dimensional imaging, the use of MRI also eliminates the problem of radiation exposure, and in some cases the images can also be useful for assessing joint inflammation.…”
Section: Image Fusionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our experience confirms previous reports on the efficacy of image fusion as a guide for sacroiliac joint injections [12] and provides the first data on the feasibility of US-MR image fusion for this purpose. Aside from the advantages of three-dimensional imaging, the use of MRI also eliminates the problem of radiation exposure, and in some cases the images can also be useful for assessing joint inflammation.…”
Section: Image Fusionsupporting
confidence: 89%
“…The limits of our study lie mainly in the small number of cases examined, which is, however, fairly similar to that of other studies reported in the literature [12]. In addition, the efficacy of the technique was documented radiologically on the basis of the registration errors, but correct intra-articular placement of the needle tip was not verified with another imaging modality.…”
Section: Image Fusionsupporting
confidence: 75%
See 2 more Smart Citations
“…The use of US fusion in the diagnosis or treatment of musculoskeletal conditions has been limited. Klauser et al [15] reported on a series of sacroiliac joint injections and showed that US and CT fusion allowed reliable injection of the target area.…”
Section: Introductionmentioning
confidence: 99%